KONSEP BELA NEGARA MELALUI NILAI-NILAI AL-QUR’AN: TELAAH TAFSIR MAUDHU’I - M. Adip Habibi; Ahmad Zainuddin; M. Mukhid Mashuri; Nyoko Adi Kusyowo (STAI Asy-Syukriyyah, 2026)
This study examines the concept of bela negara (state defense) from the Qur’anic perspective using a thematic interpretation (tafsir maudhu‘i) approach. The Qur’an does not explicitly mention nationalism or state defense in modern political terms, but these values are reflected through teachings on love for the homeland, obedience to legitimate leadership, unity, and tolerance in diversity. The study finds that state defense in the Qur’an includes not only physical protection but also moral, social, political, and spiritual responsibility. Maintaining justice, preserving national unity, and promoting social harmony are essential forms of defending the state within contemporary national life.